Cuidado parental em quatro espécies simpátricas de Leptodactylus (Anura; Leptodactylidae) - Silva, Daniele Resende da (2009)
Maternal care to tadpole shoals occur in four species of Leptodactylus that occur in the Cerrado of the Triângulo Mineiro. Here we described and quantify features of the maternal care for these species. We presented a list of behaviors related performed by the carrying females and determined if, in L. ocellatus, L. podicipinus, and L. cf. leptodactyloides these behaviors varied between the day and night. Behaviors were quantified in one hour periods of uninterrupted observation with continuous registration. Sporadic interactions among females, offspring and predators were also focal accompanied with continuous registrations. In the four species the tadpoles formed dense shoals guarded by the mother; the females performed aggressive behaviors toward predators and tadpole guidance through diving and pumping (moving up and down the pelvic girdle) behavior. In L. ocellatus the females reacted against coespecifics adults. Females of L. ocellatus, L. podicipinus, and L. cf. leptodactyloides fed during the maternal care and females of L. podicipinus and L. cf. leptodactyloides built channels for the tadpoles. There was a case of interspecific brood-mixing between shoals of L. ocellatus and L. podicipinus. Females remained around the mixed shoals and performed pumping and aggressive behaviors. Probably females cannot differentiate their offspring from conspecifics and heteroespecifics tadpoles. Fourteen behavioral categories were executed by L. ocellatus; 11 of these behaviors were exhibited also by L. podicipinus, nine by L. cf. leptodactyloides, and four by L. chaquensis. Females of L. ocellatus and L. cf. leptodactyloides were more active in the night period. For L. ocellatus the sum of the behavioral acts was correlated with the size of the tadpoles (night observations). For L. cf. leptodactyloides the behavioral categories "pumping" and "for-wards movement after pumping", were more frequent during the night. For Leptodactylus ocellatus, the categories "leave behind (shoal)", "approach", "pumping" and "for-wards movement after pumping" were more frequent at night; the category "remain under the shoal" was more frequent during the day. The smaller diurnal activity of the females may be related to the need of remain unnoticed from diurnal predators. The larger diurnal frequency of "remain under the shoal" can be related to the defense of the offspring against predators such as teleosts. The parental care features we found were similar to other closely related species of the group and can be regarded as a phylogeny constrained feature.